Neuromodulatory Effect of Thymoquinone in Attenuating Glutamate-Mediated Neurotoxicity Targeting the Amyloidogenic and Apoptotic Pathways - Fouad, Ibram Amin; Sharaf, Nadia Mohamed; Abdelghany, Ragwa Mansour; El Sayed, Nesrine Salah El Dine (Frontiers in Neurology, 2018)
Overexposure of the glutamatergic N-methyl-D-aspartate (NMDA) receptor to the excitatory neurotransmitter L-glutamic acid leads to neuronal cell death by excitotoxicity as a result of increased intracellularCa2+, mitochondrial dysfunction and apoptosis. Moreover, it was previously reported that prolonged activation of the NMDA receptor increased beta-amyloid (A) levels in the brain. Thymoquinone (TQ), the active constituent of nigella sativa seeds, has been shown to have potent antioxidant and anti-apoptotic effects. The aim of the present study was to explore the neuromodulatory effects of different doses of TQ (2.5 and 10 mg/kg) against apoptotic cell death and A formation resulting from glutamate administration in rats using vitamin E as a positive control. Behavioral changes were assessed using Y-maze and Morris water maze tests for evaluating spatial memory and cognitive functions. Caspase 3, Lactate dehydrogenase, Aβ-42, and cytochrome C gene expression were determined. TQ-treated groups showed significant decreases in the levels of all tested biochemical and behavioral parameters compared with the glutamate-treated group. These findings demonstrated that TQ has a promising neuroprotective activity against glutamate-induced neurotoxicity and this effect is mediated through its anti-amyloidogenic, antioxidant, and anti-apoptotic activities.